2019
DOI: 10.5650/jos.ess18209
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Characterization of Palm Oil-based Nanoemulsion Loaded with <i>Parthenium hysterophorus</i> Crude Extract for Natural Herbicide Formulation

Abstract: Introduction Parthenium hysterophorus is one of the world s seven most devastating and aggressive weed commonly known as carrot grass and bitter weed 1. The Asteraceae family belonging weeds were often spotted on abandoned lands, drainage and railway tracks. Parthenium hysterophorus contained allelochemical parthenin which play as a major phytotoxic compound in the plant. Allelochemical is a chemical compound that influences growth, survival, and reproduction of other organism 2. Due to its noxious ability, P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The inhibition by Thymus capitatus and Majorana hortensis nanoemulsion towards bindweeds have shown that the nanoemulsion has suppressed the weed growth by reducing more than 50% of the fresh and dry weight of both Convolvulus arvensis and Setaria viridis than the control [111]. Nanoemulsion-derived palm oil derivatives used as a pretreatment of slender buttonweed, Diodia ocimifolia seeds also indicates that it has toxicity effect towards germination and capable to inhibit at the lowest concentration of 5 g L −1 [73].…”
Section: Biologic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition by Thymus capitatus and Majorana hortensis nanoemulsion towards bindweeds have shown that the nanoemulsion has suppressed the weed growth by reducing more than 50% of the fresh and dry weight of both Convolvulus arvensis and Setaria viridis than the control [111]. Nanoemulsion-derived palm oil derivatives used as a pretreatment of slender buttonweed, Diodia ocimifolia seeds also indicates that it has toxicity effect towards germination and capable to inhibit at the lowest concentration of 5 g L −1 [73].…”
Section: Biologic Studymentioning
confidence: 99%
“…The use of palm oil as the oil phase in pesticide nanoemulsion has contributed promising stability results. The combination of palm kernel oil ester (PKOE) with Parthenium hysterophorus crude extract (PHCE) has demonstrated its ability to control Diodia ocimifolia weeds at a fairly lower concentration, 5 g L −1 [73].…”
Section: Pesticide Nanoemulsion Based On Oil Palm Derivativesmentioning
confidence: 99%
“…89 In addition, the nanoemulsion system can also be used as another way of effectively delivering biological herbicides, where the NPs are evenly dispersed on the surface of leaves, enhance the permeability of the active ingredients in weed leaves, and thus show better control effects on weeds. 90 It is believed that nanobiological herbicides that combine biological herbicides with green, inexpensive nanomaterials will play an important role in reducing environmental pollution and the sustainable and healthy development of agriculture (Fig. 6), but it is necessary to consider the compatibility of NPs with other biological agents and their specificity to plant hosts under field conditions to limit or avoid further damage to the environment and human health.…”
Section: Bioherbicides and Nanotechnologymentioning
confidence: 99%
“…The most developed and studied formulations are nanoemulsions [ 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], followed by liposomes [ 10 , 24 , 25 , 26 , 27 ], and, finally, nanoparticles [ 11 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In general, the papers have similar developments: characterization of the formulation through tests that measure particle size, PDI, and zeta potential.…”
Section: Literature Searchmentioning
confidence: 99%
“…Some papers did not develop stability studies of the formulations developed, which is an important parameter during the product development process. Only six papers conducted the stability study of the formulations tested, as shown in Table 1 [ 9 , 10 , 14 , 19 , 21 , 22 , 23 ].…”
Section: Literature Searchmentioning
confidence: 99%